English for Young Learners: Identifying Students’ Interest and Motivation in Learning English at Madrasah Ibtidaiyah - Idami, Zahratul (Universitas Pahlawan Tuanku Tambusai, 2022)
This research was conducted to identify the interest in learning English of madrasah ibtidaiyah students in Bireuen Regency, Aceh in general as well as interest in each English skill. In addition, this study also identified students' motivation to learn English. Besides, to identify the obstacles faced by madrasah ibtidaiyah students in Bireuen Regency and to know how their opportunity was in learning English were also the aims of this study. This research was a qualitative descriptive research using observations, interviews, documents, and questionnaires to collect data. The subjects in this study were 30 students of madrasah ibtidaiyah spread across Bireuen Regency. The results of this study indicated that students of madrasah ibtidaiyah in Bireuen Regency had a very high interest in learning English in general. In each skill, students' interests from the highest were listening, speaking, reading, and writing. Meanwhile, students also had high motivation in learning English. On the other hand, the results of this study also showed that although students faced obstacles in the form of limited textbooks and the difficulty in memorizing English vocabulary, they had very high opportunities in this subject.